Analysis of Bibliographic Systems Thinking: A Review in the Science Education - Rochman, Syaiful; Rustaman, Nuryani; Ramalis, Taufik Ramlan; Suhandi, Andi; Supriyadi, Supriyadi; Ismail, Ismail (KnE Social Sciences, 2024)
In the last decade research background in science, technology, and social formal education has enlarged our knowledge about complex systems. A study informing conceptual framework across disciplines which is inclusive in system thinking (ST). Its usage in science education has increased rapidly and has also been adapted and elaborated by research networks all over the world. Mix method was used in this review to illustrate ST development in science education. Tabulation of literature inquiry resulted from Scopus database was used to conduct bibliometric and literature review. The number of publications used were within the last decade, namely from 2012 up to 2022. Annotated scores were used to analyze the trend and identify popular and potential publications. Annotated network and diagram of researchers’ network together to be analyzed and identified as a group of articles and researchers in various networking roles. Infiltering relevance resulted in about 1867 publications. Bibliographic analysis identified five groups of annotated and distinctive common authors/writers according to general geography, research focus, institutional inspiration, or affiliation. As a set of loosely related science, many researchers in systems thinking have developed various system thinking aspects based on underlying perspectives. A preliminary study was inspired by education-related literature, meanwhile another group adopted the largely inclusive comprehension which combined/integrated knowledge and related system approach. System thinking is concluded as a discussion topic that was getting popular in system thinking comprehension and its approaches in science are openly probable to be studied. In depth recognizing and developing these ideas and groups of authors/writers in system thinking literature can give clarification and possibility or instruction, research, and further developments. Keywords: bibliographic, systems thinking, science education